1983
DOI: 10.1063/1.331925
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the midgap electron traps (EL2) in liquid encapsulated Czochralski GaAs

Abstract: We have characterized the midgap electron trap (so far believed to be EL2) in liquid encapsulated Czochralski GaAs by measuring deep level transient spectroscopy spectra, and found more than two midgap electron traps which can be classified into two groups. A trap belonging to the first group is rather stable in its properties and the other is unstable. The capture cross section of the levels in the latter group varies continuously in depth from the surface and also is changed by thermal annealing. We discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
20
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(28 citation statements)
references
References 4 publications
8
20
0
Order By: Relevance
“…Our argument is in conformity with the result of Huber et al [61] and Wallis et al [63]. If the 0.83 eV level was due to pure Ga vacancies in VPE samples, bulk present work, [44,49,51,55], [6,26,28,47,48,49,54,56] present work, [21,49], [25,26,29] À 2 VPE present work, [7,20,27,33,34,39,41,42,45,46] present work, [20,21,22,23,57,58], [27,61] present work, [22] 3 LPE present work, [28,32,60] [ 28,49], [32,60] present work, [30,33,34], [ 10 OMVPE-GaInAs …”
Section: Analysis and Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our argument is in conformity with the result of Huber et al [61] and Wallis et al [63]. If the 0.83 eV level was due to pure Ga vacancies in VPE samples, bulk present work, [44,49,51,55], [6,26,28,47,48,49,54,56] present work, [21,49], [25,26,29] À 2 VPE present work, [7,20,27,33,34,39,41,42,45,46] present work, [20,21,22,23,57,58], [27,61] present work, [22] 3 LPE present work, [28,32,60] [ 28,49], [32,60] present work, [30,33,34], [ 10 OMVPE-GaInAs …”
Section: Analysis and Discussionsupporting
confidence: 81%
“…Williams [25] also reported a donor level lying 0.74 eV below the conduction band edge in several n-type samples of GaAs. A level at 0.75 eV was detected by Taniguchi and Ikoma [26] in LEC-GaAs. Li et al [27] observed a similar level in several VPE crystals but the reported energy is only 0.71 eV below E c. The existence of this level in LPE material has been shown by Lang and Logan [28].…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Silvestri et al [5] have already reported a variation in capture cross-section within GaN layer with different Fe-doping level. Moreover, previous work on GaAs [6] has shown how the same trap level can yield different capture cross-sections when material growth and annealing conditions are changed. This can also be the case of the FE devices tested, where the defect related to the Fe-doping might have its capture cross-section dependent from the doping, growth or annealing conditions of the three different epi-structure.…”
Section: Trapping Phenomena In Fe Devices Analysismentioning
confidence: 98%
“…However, this level was not observed in the LPE [ 9 31 and MBE [ 9 4 ] grown GaAs epitaxial materials. Recent studies of the LEC bulk grown GaAs reported by Taniguchi et al [74] have found that Ec -0.77eV electron trap exists in the front section of LEC GaAs ingot, whereas SEc 0.82eV level is the dominant trap level appeared in tail section of the ingot.Thesame result was reported in MOCVD grown GaAs epilayersby * material can be grown only from melts above a critical As composition, and the EL2a level was native defect observed in this material. Ga-rich melts were found to yield p-type, low resistivity GaAs crystal.…”
Section: )mentioning
confidence: 99%